Automatic Rietveld refinement by robotic process automation with RIETAN-FP. Issue 1 (31st December 2022) - Tamura, Ryo; Sumita, Masato; Terayama, Kei; Tsuda, Koji; Izumi, Fujio; Matsushita, Yoshitaka
ABSTRACT: Rietveld analysis necessitates the manual trial-and-error refinement of various parameters. To reduce human costs and resources, we have developed a robotic process automation (RPA) system for the Rietveld analysis program RIETAN-FP. By executing our proposed RPA programs, the background parameters of intensities can be determined, and black-box optimizations used to automatically search for peak profile parameters with a small R w p value. Additionally, we evaluated the programs for analyzing X-ray powder diffraction patterns of anatase TiO2, Ca5 (PO4 )3 F, and BaSO4 . Consequently, it was verified that RPA can be utilized to automate Rietveld analysis in simple cases. This indicates that RPA can be used for conducting black-box optimizations for graphical user interface (GUI) applications in materials science. Graphical abstract: uf0001